2019
DOI: 10.1111/jocn.14953
|View full text |Cite
|
Sign up to set email alerts
|

The symptoms, resourcefulness and quality of life in community‐based patients with schizophrenia

Abstract: Aims and objectives To test Zauszniewski's resourcefulness and quality of life theory in community‐based patients with schizophrenia. The objectives were to: (a) examine the relationship among psychotic symptoms, resourcefulness and quality of life, and (b) explore the determinants of quality of life. Background According to Zauszniewski's resourcefulness and quality of life theory, for patients, the skills constituting resourcefulness should centre on helping oneself or the use of resources to achieve their h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…A cross‐sectional study found that psychotic symptoms were determinants of quality of life for patients with schizophrenia and suggest providing interventions to train patients’ ability in self‐help and seeking help from others in order to promote skills of symptom management. One of such interventions could be PCA (Yu et al., 2019). It could be interesting to investigate what effect PCAs have after several years, since one can imagine that for some patients, it is a learning process to use their contract and that MHPs build experiences that can influence the perceived perspectives.…”
Section: Discussionmentioning
confidence: 99%
“…A cross‐sectional study found that psychotic symptoms were determinants of quality of life for patients with schizophrenia and suggest providing interventions to train patients’ ability in self‐help and seeking help from others in order to promote skills of symptom management. One of such interventions could be PCA (Yu et al., 2019). It could be interesting to investigate what effect PCAs have after several years, since one can imagine that for some patients, it is a learning process to use their contract and that MHPs build experiences that can influence the perceived perspectives.…”
Section: Discussionmentioning
confidence: 99%
“…Hwu in 1986 and has been widely used in psychiatric settings, with favourable psychometric properties (Yu et al, 2019). In this study, Cronbach's α was 0.75 for the scale.…”
Section: Brief Psychiatric Rating Scalementioning
confidence: 64%
“…A higher total score indicates more severe psychiatric symptoms and the total score ranges from 0–108. The Taiwanese version of this scale was translated by Dr. Hwu in 1986 and has been widely used in psychiatric settings, with favourable psychometric properties (Yu et al., 2019). In this study, Cronbach's α was 0.75 for the scale.…”
Section: The Studymentioning
confidence: 99%
“…According to a study conducted by Yilmaz et al [13] , individuals diagnosed with schizophrenia experienced notable enhancements in both their positive and negative symptoms after undergoing psycho-educational therapy. According to Young [14] , a study found that 92% of patients with schizophrenia experienced a decrease in impulsivity after participating in a psycho-educational program compared to before the program. Implementing a nursing educational program focused on positive and negative symptoms, as well as impulsivity, in schizophrenic patients is a practical approach to enhancing patient's understanding of their condition and diminishing the severity of these symptoms.…”
Section: Significance Of the Studymentioning
confidence: 99%